3,5,6-trichloro-2-pyridinyloxyacetic acid as effective thinning agent for fruit of 'Montenegrina' mandarin - Mateus Pereira Gonzatto; Gerson Nestor Böettcher; Leonardo André Schneider; Ângelo Azeredo Lopes; Jairo Camargo Silveira Júnior; Henrique Belmonte Petry; Roberto Pedroso de Oliveira; Sergio Francisco Schwarz (Ciência Rural)
ABSTRACT: The 'Montenegrina' mandarin ( Citrus deliciosa Tenore) is widely cultivated in southern Brazil. This cultivar has a great tendency for alternate bearing, requiring thining of the fruit. However, the chemical thinners studied until now in this cultivar have not been successful. The objective of this research was to evaluate the effect of 3,5,6-trichloro-2-pyridinyloxyacetic acid (3,5,6-TPA) on the production and fruit quality of the 'Montenegrina' mandarin, in comparison with hand thinning and the options of chemical thinning previously studied. Hand thinning and no thinning were used as controls. Ethephon was applied in three doses: 200mg L-1, 300mg L-1 or 200mg L-1 + 3% urea; or 3,5,6-TPA, in four doses: 10, 20, 30 or 40mg L-1. Fruits of the hand thinned trees and those treated with 40mg L-1 showed greater average size, greater distribution of commercial caliber and more orange colors. No treatment reduced alternate bearing. Applications of 40mg L-1 of 3,5,6-TPA as a chemical thinner, during the physiological drop of young fruit, had a similar effect that of hand thinning over yield and quality of fruits of 'Montenegrina' mandarin.